Evaluation of a single extraction test to estimate the human oral bioaccessibility of potentially toxic elements in soils: towards more robust risk assessment - Rodrigues, S. (2020)
Intake of soil by children and adults is a major exposure pathway to contaminants including potentially toxic elements (PTEs). However, only the fraction of PTEs released in stomach and intestine are considered as bioaccessible and results from routine analyses of the total PTE content in soils, therefore, are not necessarily related to the degree of bioaccessibility. Experimental methods to determine bioaccessibility usually are time-consuming and relatively complicated in terms of analytical procedures which limits application in first tier assessments. In this study we evaluated the potential suitability of a recently developed single extract method (ISO-17586:2016) using dilute (0.43M) nitric acid (HNO3) to mimic the bioaccessible fraction of PTEs in soils. Results from 204 soils from Portugal, Brazil and the Netherlands including all major soil types and a wide range of PTEs' concentrations showed that the extraction efficiency using 0.43M HNO3 of Ba, Cd, Cu, Ni, Pb and Zn in soils is related to that of in vitro methods including the Simple Bioaccessibility Extraction Test (SBET) and Unified BARGE Method (UBM). Also, differences in the degree of bioaccessibility resulting from differences in parent material, geology and climate conditions did not affect the response of the 0.43M HNO3 extraction which is a prerequisite to be able to compare results from different soils. The use of 0.43M HNO3 as a first screening of bioaccessibility therefore offers a robust and representative way to be included in first tier standard soil tests to estimate the oral bioaccessibility.